Peningkatan Keterampilan Menulis Teks Prosedur Menggunakan Model Read Answer Discuss Explain Create (RADEC) pada Peserta Didik Kelas V SD Negeri 29 Batang Anai Kabupaten Padang Pariaman - Ardeliani, Rahmania Yuni; Sukma, Elfia (Lembaga Intelektual Muda (LIM) Maluku, 2025)
This research aims to describe improving procedural text writing skills using models Read Answer Discuss Explain Create (RADEC). The subjects of this research were teachers as observers and 22 class V students as participants. The approach used is a qualitative and quantitative approach. This type of research is Classroom Action Research (CAR) which is carried out in two cycles, namely cycle I consisting of 2 meetings and cycle II consisting of 1 meeting. Each cycle includes four stages, namely planning, implementation, observation and reflection. Data collection techniques include tests, non-tests, observations and document analysis. The results of the research showed that there was an increase in the aspects of the teaching module in cycle I which obtained an average of 88.75% (B) and in cycle II obtained an average of 95% (SB). The teacher's implementation of learning aspects in cycle I obtained an average of 80.36% (B) and in cycle II it increased to 96.42% (SB). The implementation of learning aspects of students in cycle I obtained an average of 80.36% (B) and at cycle II increased to 96.42% (SB). Student learning outcomes in cycle I obtained an average of 75.94 (C) and in cycle II it increased to 88.42 (B). Thus, model Read Answer Discuss Explain Create (RADEC) can improve students' procedural text writing skills in class V of SDN 29 Batang Anai